Volatile Compounds Detected in Coconut Shell Liquid Smoke through Pyrolysis at a Fractioning Temperature of 350-420 C - Hadanu, Ruslin; Apituley, Daniel Ambrosius Nicholas (UI Scholars Hub, 2016)
This study evaluated the volatile components of liquid smoke from coconut shells obtained through the pyrolysis process at fraction 350-420 °C. The volatile compounds of liquid smoke from a coconut shell were analyzed using gas chromatography and mass spectrometry (GC-MS). Nineteen peaks were detected by GC-MS in the coconut shell liquid smoke, and 19 compounds also were identified. The volatile compounds were identified as follows based on their function group’s composition percentage: phenol (90.75%), carbonyl (3.71%), alcohol (1.81%), and benzene (3.73%), respectively. The liquid smoke contains a high ratio of phenol derivatives (90.75%) in volatile profile. The phenol derivatives were the major volatile compounds found in the coconut shell liquid smoke.